Human Resource Management: Adapting Leadership in Managing Teams in a Hybrid Working System - Setyowati Subroto (PT. Hafasy Dwi Nawasena, 2026)
The hybrid working system has become a dominant work model in modern organizations, combining remote and onsite work arrangements to improve flexibility and operational efficiency. However, the implementation of hybrid work also presents significant managerial challenges, particularly in maintaining team cohesion, communication effectiveness, employee engagement, and performance management. This article aims to analyze how leadership adaptation plays a critical role in managing teams under hybrid working systems within the framework of Human Resource Management. Using a qualitative approach through a literature review method, data were collected from reputable academic journals and scholarly books discussing telecommuting, e-leadership, adaptive leadership, transformational leadership, and organizational behavior. The analysis was conducted through descriptive-qualitative techniques involving data reduction, thematic categorization, and interpretation. The findings indicate that effective leadership in hybrid working environments requires the development of digital leadership competencies, trust-based management, flexible communication strategies, and performance evaluation systems focused on outcomes rather than physical presence. Moreover, adaptive and transformational leadership styles are essential in addressing emerging challenges such as workplace loneliness, blurred work-life boundaries, and reduced team collaboration. This study concludes that leadership adaptation is a strategic determinant of organizational success in hybrid working implementation and highlights the importance of integrating leadership development into HRM strategies to sustain productivity and employee well-being.